Electronic prescription as a driver for digitalization in Finnish pharmacies - Peltoniemi Teijo; Suomi Reima; Peura Sirpa; Lähteenoja Markus (BioMed Central, 2025)
Background
Finnish community pharmacies have undergone digitalization during the past decade. The introduction of the electronic prescription has had a significant impact on pharmacy workflows, such as the dispensing process. This inevitably has significant sociotechnical implications. We examine the impact of digitalization on the dispensing process and the sociotechnical orientation of a pharmacy.
Methods
We utilize data collected in customer service situations in Finnish community pharmacies at two points in time: in the traditional workflow, when electronic prescriptions were not in use, and in the new direct dispensing workflow, which is the usual delivery model in the case of electronic prescriptions. We analyze this data in terms of changes in workflow efficiency. We also draw on existing literature to build a conceptual model for digitalization in the pharmacy sector from a sociotechnical standpoint.
Results
In the Finnish environment, the results, based on our study sample, show that with electronic prescriptions and the direct dispensing model, the delivery time for a single medication over the counter was reduced by 13%. The results also indicate that the process has become more predictable, as the variation in terms of the workflow lead time has decreased.
Conclusions
The results indicate that the dispensing process has become more efficient in terms of time and throughput as well as more technically oriented and predictable. From a sociotechnical perspective, the results indicate that the technical subsystem has strengthened, and pharmacies have adapted to the new technology in the dispensing process.